Livestock in Evolving Foodscapes and Thoughtscapes - Leroy, Frédéric; Hite, Adele H.; Gregorini, Pablo (Frontiers in Sustainable Food Systems, 2020)
Humanity’s main societal and epistemic transitions also mirror changes in its approach to the food system. This particularly holds true for human–animal interactions and the consumption of animal source foods (red meat especially, and to a lesser degree dairy, eggs, poultry, and fish). Hunter-gathering has been by far the longest prevailing form of human sustenance, followed by a diffuse transition to crop agriculture and animal husbandry. This transition eventually stabilized as a state-controlled model based on the domestication of plants, animals, and humans. A shift to a post-domestic paradigm was initiated during the 19th century in the urbanizing populations of the Anglosphere, which was characterized by the rise of agri-food corporations, an increased meat supply, and a disconnect of most of its population from the food chain. While this has improved undernutrition, various global threats have been emerging in parallel. The latter include, among others, a public health crisis, climate change, pandemics, and societal class anxieties. This state of affairs is an unstable one, setting the conditions of possibility for a new episteme that may evolve beyond mere adjustments within the business-as-usual model. At least two disruptive scenarios have been described in current food discourses, both by scientists and mass media. Brought to its extreme, the first scenario relates to the radical abolishment of livestock, rewilding, a ‘plants-only’ diet, and vegan ideology. A second option consists of a holistic approach to animal husbandry, involving more harmonic and richer types of human–animal–land interactions. We argue that – instead of reactive pleas for less or none – future thoughtscapes should emphasize ‘more of the better.’